Evaluation of muscle strength and range of motion of upper extremity in breast cancer-related lymphedema (Annals of Medical Research, 2026)
Aim: The objective of this study was to examine the impact of lymphedema on the muscle strength and range of motion of the upper extremities in breast cancer patients with lymphedema.Materials and Methods: Thirty-one female breast cancer survivors with lymphedema were evaluated in this cross-sectional study. The measurement of shoulder, elbow, and wrist flexion and extension strength was conducted using a hand-held dynamometer on both affected and unaffected upper extremities. Subsequently, a digital goniometer was utilized to assess the range of motion in both the affected and unaffected upper extremities.Results: A median age of 61 years (with an interquartile range of 55 to 69 years) was reported for the patients, and dominant right upper extremity was noted for all. The study revealed that the affected extremity exhibited reduced shoulder flexion and extension muscle strength and range of motion, and decreased elbow flexion muscle strength when compared to the unaffected upper extremity (p0.05).Conclusion: In cancer-associated lymphedema, limitations in muscle strength and range of motion are primarily localized to the shoulder region. These findings may serve as a guide for clinicians in the development of targeted rehabilitation interventions, with the aim of restoring mobility and strength in the areas most affected by lymphedema.
Keywords: Lymphedema; Muscle strength; Range of motion